1998
DOI: 10.1017/s0031182098002455
|View full text |Cite
|
Sign up to set email alerts
|

Host searching in Argulus foliaceus L. (Crustacea: Branchiura): the role of vision and selectivity

Abstract: In laboratory experiments the swimming behaviour of the ectoparasite Argulus foliaceus and its infection rates on juvenile perch (Perca fluviatilis) and roach (Rutilus rutilus) were examined. The highest infection rate and a preference for perch juveniles were obtained in darkness, the lowest infection rate and a lack of preference in the light, when aquaria with glass walls (high reflectivity) were used. In the light, when aquaria were lined with black plastic (low reflectivity) an intermediate level of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Previous authors have demonstrated differences in the behaviour of Argulus foliaceus between periods of light and dark with respect to their host finding strategies, the highest infection rate being in times of darkness (Mikheev et al 1998). Also, it has been shown that A. foliaceus adopts different strategies for host finding between dark and light conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors have demonstrated differences in the behaviour of Argulus foliaceus between periods of light and dark with respect to their host finding strategies, the highest infection rate being in times of darkness (Mikheev et al 1998). Also, it has been shown that A. foliaceus adopts different strategies for host finding between dark and light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that water lice, therefore, mainly lay their eggs during the night at fish farms. His work, however, was conducted in an experimental setting where host availability is perhaps likely to be artificially high and, hence, natural host finding and egglaying behaviours may not be exhibited.Previous authors have demonstrated differences in the behaviour of Argulus foliaceus between periods of light and dark with respect to their host finding strategies, the highest infection rate being in times of darkness (Mikheev et al 1998). Also, it has been shown that A. foliaceus adopts different strategies for host finding between dark and light conditions.…”
mentioning
confidence: 99%
“…The observed differences in the growth rate and size of Argulus coregoni reared on rainbow trout and roach was also related to differences in their residence time on the 2 species. At a size of 2 mm, an ontogenetic shift in host choice occurred, with their initial preference for the brighter and more easily recognizable roach (Mikheev et al 1998) changing to a highly pronounced preference for rainbow trout (Mikheev et al 2004). This could be the main reason for their more frequent detachment from roach.…”
Section: Discussionmentioning
confidence: 99%
“…In situations where equal numbers of equal sized hosts are present at the same time, host species preferences of A. foliaceus may become more apparent. Mikheev et al (1998) studied this situation on roach, Rutilus rutilus (L.), and perch, Perca fluviatilis (L.), and found that perch were generally favoured over roach. There are only a few studies investigating host preferences by A. foliaceus and this could be due in part to its universal acceptance as a generalist.…”
Section: Introductionmentioning
confidence: 99%